2017
DOI: 10.1002/jmri.25634
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of arterial transit time and renal blood flow using pseudocontinuous ASL MRI with multiple post‐labeling delays: Feasibility, reproducibility, and variation

Abstract: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:813-819.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 37 publications
7
37
0
Order By: Relevance
“…Our ASL values for cortical renal perfusion are in agreement with those obtained at 3 T using breath-hold multi-TI sequences: 151 ± 37 to 215 ± 65 ml/min/100 g [20,21], but even in healthy volunteers at this field strength single-TI values range between 229 ± 41 to 327 ± 63 ml/min/100 g [10,11,26]. This variation can be attributed to different acquisition schemes, kinetic models and study populations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our ASL values for cortical renal perfusion are in agreement with those obtained at 3 T using breath-hold multi-TI sequences: 151 ± 37 to 215 ± 65 ml/min/100 g [20,21], but even in healthy volunteers at this field strength single-TI values range between 229 ± 41 to 327 ± 63 ml/min/100 g [10,11,26]. This variation can be attributed to different acquisition schemes, kinetic models and study populations.…”
Section: Discussionsupporting
confidence: 84%
“…Previous work has relied on acquiring data at multiple inversion times during separate breath-holds at 3 T [20,21], or using prospective respiratory gating at 1.5 T [22,23]. The disadvantage of prospective gating is that it prolongs acquisition time unnecessarily if separation of respiratory phases is not required.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous ASL (CASL) and pulsed ASL (PASL) are novel labeling schemes that provide better labeled magnetization deliveries and a higher SNR than previous labeling methods, without the need for an additional modified RF amplifier . Kim et al evaluated the feasibility and reproducibility of pseudocontinuous ASL (pCASL) MRI with multiple postlabeling delays (PLDs) . They found that medullar perfusion showed substantial variations that could not be used in further studies.…”
Section: Renal Fmrimentioning
confidence: 99%
“…Multiple PLDs help to compensate for the underestimation due to the partial mismatch or overestimation due to areas near large vessels. However, this correction may not be necessary in healthy populations …”
Section: Renal Fmrimentioning
confidence: 99%
“…Recent studies have proposed volumetric acquisitions with spiral readouts using 3D fast/turbo spin echo (FSE/TSE) sequence for increased SNR (17). However, EPI and spiral readouts have limitations in body applications due to the association between worse off-resonance effects and larger fields of view (18). Cartesian based TSE readout using single-shot (SSFSE/SShTSE/HASTE) or segmented 3D TSE are robust options for perfusion imaging in body applications (19).…”
Section: Perfusion Imaging: Techniquesmentioning
confidence: 99%